Nitrate Metabolism and Ischemic Cerebrovascular Disease: A Narrative Review - Wang, Yicong; Chen, Weiqi; Zhou, Jian; Wang, Yongjun; Wang, Hao; Wang, Yilong (Frontiers in Neurology, 2022)
Inorganic and organic nitrates are present in vivo and in vitro. Inorganic nitrate is considered a pool of nitric oxide (NO), but it can be converted into nitrite and NO through various mechanisms, and plays an important role in the regulation of complex physiological and biochemical reactions, such as anti-inflammatory processes and the inhibition of platelet aggregation, which are closely related to the pathology and treatment of cerebrovascular disease. Ischemic cerebrovascular disease is characterized by high incidence, recurrence and disability rates. Nitrate, nitrite and NO were recently found to be involved in cerebrovascular disease. In this review, we describe the relationship between cerebrovascular disease and nitrate metabolism to provide a basis for further advances in the laboratory and clinical settings.